THE MORALITY OF LYING TO MY GRANDPARENT WITH DEMENTIA. (16th November 2018) - Ebert, A; Miron, A; Hodel, A
Abstract: We used Gilligan's (1982) morality of care theory to examine how grandchildren cope with having to deceive or lie to their grandparent with dementia. Data from individual semi-structured interviews with thirteen young adults were analyzed using Interpretative Phenomenological Analysis. We found that a moral orientation shift toward a person-centered morality of care occurs gradually. Grandchildren struggle with concepts of moral goodness, importance of close others, and questions about self as a moral agent. We uncovered three antecedents of this shift: (1) severity of dementia symptoms, (2) valuing of the grandparent's welfare, and (3) valuing of the relationship. Further, we discovered this shift has three outcomes: (1) transformation of self as a moral agent (experienced emotions become guides to moral behavior, the morality of care orientation affects moral appraisals, behaviors, and emotions within and outside of the grandchild-grandparent relationship), (2) changed relationship with the grandparent, and (3) changed family dynamics and relationships. Current ethics and legislation assume the presence of a common shared world for both people with dementia and their family members (Hertogh et al., 2004). However, when people with dementia no longer share the same reality as their family members, it may be more difficult to use these common ethical standards to guide ethical decisions (Hasselkus, 1997; Hertogh et al., 2004; Moody, 1988; Schermer, 2007). Consequently, work is needed to develop new guidelines for family interactions that take these complex moral issues into consideration.